Departmental Context and Formal Structure as Constraints on Leader Behavior - Ford, Jeffrey D. (Academy of Management Journal, 1981)
An empirical investigation was made of the effects of size, personnel education, task routineness, workflow interdependence, environmental uncertainty, and formal structure on the behavior of leaders. Task routineness, personnel education, and environmental uncertainty were found to influence leader initiating structure; size and personnel education had a significant relationship to leader consideration.